การศึกษาสมรรถนะของพยาบาลวิชาชีพในหน่วยงานแผลไฟไหม้- น้ำร้อนลวกโรงพยาบาลตติยภูมิ - วีณา ไลชาติกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The purpose of this research was to describe the nursing competency in burn unit, tertiary hospitals, using EDFR technique. Participants were 25 experts including 3 committee members from the Thai Nursing Council, 8 nursing administrators, 7 staff nurses, and 7 physicians with burn specialty. The EDFR technique consisted of 3 steps. Step I. all experts were asked to describe competency of the nurse on Burn unit of the tertiary hospitals. Step 2, study data were analyzed by using content analysis to search for themes involving competency. Then those themes were developed for the study questionnaire. All items contained in the questionnaire were ranked the level of competency by a prior panel of experts. Step 3, items were analyzed by using mean and interquatile range and then a new version of the questionnaire was developed. The new questionnaire was sent to previous experts for confirming the previous ranked items. Ranked items were analyzed again by using mean and interquatile range to summarize the competency of the nurse on Burn unit. The major findings were as follows: The nursing competency of the nurse on burn unit, tertiary hospitals were classified into two groups consisting of six components. 1. General nursing competency was consisted of 3 components : 1.1 Personal characteristics. 1.2 General nursing care 1.3 Leadership 2. Specific nursing competency was consisted of 3 components : 2.1 Knowledge of burn care 2.2 Nursing skill of burn care 2.3 Nursing ability of burn care.